Clostridium difficile infection a public health problem - Bednarek, Jadwiga Janina (Journal of Education, Health and Sport, 2018)
Clostridium difficile is a Gram-positive rod that produces spores that are commonly found in animals, humans and the environment. Asymptomatic carriage of Clostridium difficile occurs in 3 15% of healthy adult population and increases up to 20-30% in hospitalized patients [1,2]. The number of nosocomial and non-hospital infections caused by the Clostridium difficile is increasing. The number of relapses is also increasing. In older patients with multi-organism, the serious course of the disease is more and more often observed. Multi-organism and the associated necessity to apply therapeutic activities disturb the homeostasis of the intestinal microbiome. Important factors disturbing the balance, favoring the occurrence of diarrhea symptoms and Clostridium difficile infection are: pharmacotherapy (mainly antibiotics, steroids, proton pump inhibitors) and past inflammations and procedures of the gastrointestinal tract. Fast identification of a pathogen in a stool sample taken from a patient with diarrhea is of therapeutic and, above all, epidemiological significance. Awareness of the existing threat, the use of effective prevention and isolation of infected patients and effective decontamination of the hospital environment gives hope for reducing the incidence of CDI.